2006
DOI: 10.1161/01.atv.0000235605.51400.9d
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adipose Tissue Development by Pharmacological Inhibition of PAI-1

Abstract: Objective-The effect of a novel small molecule plasminogen activator inhibitor (PAI-1) inhibitor on adipose tissue physiology was investigated. Methods and Results-In human preadipocyte cultures, PAI-039 inhibited both basal and glucose-stimulated increases in active PAI-1 antigen, yet had no effect on PAI-1 mRNA, suggesting a direct inactivation of PAI-1. Differentiation of human preadipocytes to adipocytes was associated with leptin synthesis, which was significantly reduced in the presence of PAI-039, toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 55 publications
4
55
0
1
Order By: Relevance
“…This indicates PAI‐1 may play a role in glucose regulation and is consistent with previous population studies that reported positive correlations between circulating PAI‐1 and glucose levels 6, 51, 52. In addition to observational studies, experimental studies showed that PAI‐1 deficiency via genetic knock‐out or pharmacological inhibition can suppress the levels of blood glucose in mice 53, 54. MR analysis of PAI‐1 with type 2 diabetes mellitus had a consistent effect direction with what is expected based on the glucose findings, but was not significant (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…This indicates PAI‐1 may play a role in glucose regulation and is consistent with previous population studies that reported positive correlations between circulating PAI‐1 and glucose levels 6, 51, 52. In addition to observational studies, experimental studies showed that PAI‐1 deficiency via genetic knock‐out or pharmacological inhibition can suppress the levels of blood glucose in mice 53, 54. MR analysis of PAI‐1 with type 2 diabetes mellitus had a consistent effect direction with what is expected based on the glucose findings, but was not significant (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…ACE converts angiotensin I into angiotensin II, and in humans, angiotensin II increases the expression of PAI-1, whereas inhibition of ACE decreases PAI-1 in plasma and tissues (Brown et al 1998(Brown et al , 1999. In the mouse, inhibition of PAI-1 has been associated with reduced weight of fat depots and adipocyte size (Crandall et al 2006). Influence of ACE on tissue plasminogen activator (tPA) has also been reported, but remains controversial (Brown et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although an inhibitor for PAI-1 that neutralizes the activity of both PAI-1 in complex with VN and of free PAI-1 may yield the most effective inhibition, it is still possible that selective inhibition of free PAI-1 could provide therapeutic benefit. Several studies with inhibiting antibodies and small molecules against PAI-1 have shown effects in different animal models of fibrinolysis (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). We are not aware of a PAI-1 inhibitor that has been tested in patients, but the low molecular weight PAI-1 inhibitor PAI-749 (diaplasinin) has been tested ex vivo in human blood using the Badimon chamber and was found not to have an effect on in vitro or ex vivo thrombus formation or fibrinolysis in the presence or absence of tPA (43,44).…”
mentioning
confidence: 99%